Impact of Information System on Firm's Performance: Small and Medium Enterprises in Bangladesh - Azim, Md. Shamimul (2011)
The challenge before Bangladesh today is how to make her existing SMEs compete with their equal-level rivals from abroad by modernizing themselves with up-to-date technologies and production processes. Along with that comes the question of how to develop the culture and practice of setting up new industries able to thrive in global competition right from the beginning Globalization, as one knows, has not only challenges but also enormous opportunities for those who have the capability of utilizing them. For them to the most important issue will be choice of correct technology. The main purpose of this study is to investigate the impact of information system in SMEs performance in Bangladesh. To accomplish this objective sample has been selected from industrial area in Dhaka Bangladesh and questionnaire was distributed to the respondents. There is positive relationship has found among ease of use, skills and knowledge and information quality with SMEs performance in Bangladesh.